Improving Government's Performance Management by Using the Balanced Scorecard on Stakeholders Perspectives - Suyuti Marzuki; Bambang Shergi Laksmono; Athor Subroto (Journal of the Community Development in Asia (JCDA), 2020)
On the occasion of the Government Bureaucracy Reform implementation, especially the 7th program, Performance Accountability Strengthening, ministries and institutions (K/L) of the government continue to work to build a better performance management system. Recently, in the democratization and globalization era, the measurement of organization performance is an urgent task for a good government. Thus, a modern performance management is needed to provide transparency on performance accountability through a government performance management system mandated in the governance reform. Performance management is the process of developing shared understanding of (1) what will be achieved, (2) how to achieve the performance, and (3) what approach to improve performance achievement. Performance Accountability of Government Institution System (SAKIP) is a reform model to realize the good governance from the issuance of the MPR Decree XI/1998 and Law No. 28/1999 concerning clean and free of corruption state through the principles of good state administration (Law No. 28/1999), one of which is accountability. The Balanced Scorecard (BSC) with four perspectives is a highly effective method of measuring and managing performance to enhance accountability (the seventh principle) through the integration of government planning and budgeting systems, at the central, provincial and municipal levels. In addition, BSC is integrated between internal levels of government organizations from the vision of the government organization's mission as well as Strategic Objectives (SS) and the Key Performance Indicators (IKU). Furthermore, BSC with the cascade and alignment methods can be used as a tool to improve the organizational structure and functions. This study focuses on the measurement of accountability and improving the performance of government organizations in achieving the social impacts of development outcomes. The statistical test results of the significance outcomes of the MMAF (Ministry of Marine Affairs and Fisheries) based on the maximum standard of the accountability value as defined by the Ministry of Administrative and Bureaucratic Reform, is an average of above 0.5 (95%), while the achievement of organizational performance with the BSC stakeholders perspective is 132.51% (2015), 118.3% (2016), and 99.05% (2017).